The Impact of Technological and Structural Changes in the National Economy on the Labour-Capital Relations - Małgorzata Gawrycka; Aneta Sobiechowska-Ziegert; Anna Szymczak (Contemporary Economics)
The aim of the research presented in this paper is to show the relations between labour and capital in the national economy, resulting from technological and structural changes taking place in the years 1991 to 2008 and to indicate of their importance for economic growth. The paper presents the functional determinants for the Polish economy in 1991-2008 affecting the phenomenon subject to study as well as the preliminary analysis of relations between capital and labour and their impact on the GDP. In the research the econometric methods of description and inference based on the concept of macroeconomic Cobb-Douglas production function in both static and dynamic approach were used. The study shows that increase in production in the national economy was largely the result of capital growth during the analysed period. The main factor of economic growth however in the years 1998 to 2008 was the technological progress. The results may be the implication for economic policy in terms of investment and employment.